Analyzing T Cell Responses How to analyze cellular immune responses against tumor associated antigens - Nagorsen, Dirk.; Marincola, Francesco M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
Active specific immunotherapy is a promising but investigational modality in the management of cancer patients. Currently, several different cancer vaccine formulations such as peptides, proteins, antigen-pulsed dendritic cells, whole tumor cells, etc. in combination with various adjuvants and carriers are being evaluated in clinical trials (1-3). To determine the optimal cancer vaccine strategy, a surrogate immunological end-point that correlates with clinical outcome needs to be defined, since it would facilitate the rapid comparison of these various formulations. Traditional immunological assays such as ELISA, proliferation and cytotoxicity assays can detect immune responses in vaccinated patients but are not quantitative. In contrast, novel assays such as enzyme-linked immunospot (ELISPOT) assay, intracellular cytokine assay and tetramer assay can quantitate the frequency of antigen-specific T cells. Of these, the ELISPOT assay has the 5 lowest detection limit with 1/10 peripheral blood mononuclear cells (PBMC) and has been determined to be one of the most useful assays to evaluate immune response to cancer vaccines (4). However, the IFN-? ELISPOT assay is not an exclusive measure of cytotoxic T-lymphocyte (CTL) activity as non-cytotoxic cells can also secrete IFN-?. Additionally, CTL with lytic activity do not always secrete IFN-? (5). A more relevant approach to assess functional activity of cytotoxic lymphocytes would be to measure the secretion of molecules that are associated with lytic activity. One of the major mechanisms of cell-mediated cytotoxicity involves exocytosis of cytoplasmic granules from the effector toward the target cell.
Monitoring Antigen-Specific T Cell Responses -- Tumor Associated Antigens -- Immune Escape, Tumor induced immune suppression and immune escape: Mechanisms and Possible Solutions -- Virus Specific T-Cell Responses -- Cytotoxicity Assays Killer Lymphocytes in Cancer -- Monitoring T Cell Proliferation -- Elispot Assay, Assessment of Cellular Immune Responses to Anti-Cancer Vaccines -- Modified Elispot, Modifications of the Elispot Assay for T Cell Monitoring in Cancer Vaccine Trials -- Intracellular Cytokine Staining, Cytokine flow cytometry for characterization of tumor-specific T cell responses -- Cytometric Cytokine Secretion Assay, Detection and Isolation of Antigen-Specific T Cells -- Peptide/MHC Tetramer Analysis -- In Situ MHC Tetramer Staining, In Situ Tetramers -- MHC-IG Dimeric Molecules, Dimers - MHC-IG dimeric molecules for the analysis of antigen-specific T cell responses -- TCR Analyses, T-cell receptor CDR3 analysis: Molecular fingerprinting of the T-cell receptor repertoire -- Peptide/HLA-GFP Complexes, Detection of Antigen-Specific T Cells by Acquisition of Peptide/Hla-Gfp Complexes -- QRT-PCR, Quantitative RT-PCR for the Analysis of T cell Responses in Immunized Cancer Patients -- Microarrays, Gene expression profiling approaches for the monitoring of anti-cancer immune responses -- Concluding Remarks.
Keywords: Immunology; Cancer research; Hematology; Blood transfusion; Virology; Immunology; Cancer Research; Hematology; Blood Transfusion Medicine; Virology